Bailey & Love's short practice of surgery - Bulstrode, C. J. K; Russell, R. C. G; Williams, Norman S., 1947- (Arnold, 2000)
This edition offers information on trauma, orthopaedic surgery, plastic surgery, neurosurgery and maxillofacial surgery. Chapters have been added to include the role of radiology in surgical practice, surgical ethics among others
Previous edition: London: Chapman & Hall, 1995
Keywords: Tp Fakultesi Kutuphanesi; Surgery.; Cerrahi; General Surgery